HIV-Related Risk Behaviors Among the General Population: A Survey Using Audio Computer-Assisted Self-Interview in 3 Citiesin Vietnam. (March 2015) - Vu, Lan T H; Nadol, Patrick; Le, Linh Cu
This study used a confidential survey method—namely, Audio Computer-Assisted Self-Interview (ACASI)—to gather data about HIV-related risk knowledge/behaviors among the general population in Vietnam. The study sample included 1371 people aged 15 to 49 years in 3 cities—Hanoi, Da nang, and Can Tho. Results indicated that 7% of participants had ever had nonconsensual sex, and 3.6% of them had ever had a one-night stand. The percentage of male participants reported to ever have sex with sex workers was 9.6% and to ever inject drugs was 4.3%. The proportion of respondents who had ever tested for HIV was 17.6%. The risk factors and attitudes reported in the survey indicate the importance of analyzing risk behaviors related to HIV infection among the general population. Young people, especially men in more urbanized settings, are engaging in risky behaviors and may act as a "bridge" for the transmission of HIV from high-risk groups to the general population in Vietnam.